Solid Phase Microextraction Recent Developments and Applications - Ouyang, Gangfeng; Jiang, Ruifen; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2017)
This book offers comprehensive information on the developments and applications of the solid phase microextraction (SPME) technique. The first part of the book briefly introduces readers to the fundamentals of SPME, while subsequent sections describe the applications of SPME technique in detail, including environmental analysis (air, water, soil/sediments), food analysis (volatile/nonvolatile compounds), and bioanalysis (plants, animal tissues, body fluids). The advantages and future challenges of the SPME technique are also discussed. Including recent research advances and further developments of SPME, the book offers a practical reference guide and a valuable resource for researchers and users of SPME techniques. The target audience includes analytical chemists, environmental scientists, biological scientists, material scientists, and analysts, as well as students at universities/institutes in related fields. Dr. Gangfeng Ouyang is a Professor at the Schoolof Chemistry and Chemical Engineering, Sun Yat-sen University, China. Dr. Ruifen Jiang is an Associate Professor at the School of Environment, Jinan University, China.
Introduction of SPME -- Development of Novel Solid-Phase Microextraction Fibers -- Application of Solid Phase Microextraction (SPME) in Gas Sampling -- Application of SPME for Complex Aqueous Sampling -- Application of SPME for Aqueous Sampling -- Application of SPME for Soil and Sediment Analysis -- Application of Solid-Phase Microextraction Combined with Derivatization for Polar Compound Sampling in Environmental Analysis -- Application of SPME in Food Analysis - Flavor and Off-flavor Sampling -- Applications of in vivo and in vitro Solid-Phase Microextraction Techniques in Plant Analysis -- Solid-phase Microextraction in Binding Studies.
Keywords: Analytical chemistry; Environmental monitoring; Biomedical engineering; Food science; Analytical Chemistry; Environmental Monitoring; Biomedical Engineering and Bioengineering; Food Science